Chromosomal deletions in banana somaclonal variants reveal negative regulators of immunity underlying Fusarium wilt resistance - Puyam Tondonba Singh; Bo-Han Hou; Yi-Heng Tsai; Yuh Tzean; Chih-Ping Chao; Po-Xing Zheng; Yao-Cheng Lin; Wei-Chiang Shen; Hsin-Hung Yeh; Ho-Ming Chen (Proceedings of the National Academy of Sciences, 2025)
Fusarium wilt, caused by Fusarium oxysporum f. sp. cubense tropical race 4 (TR4), poses a severe threat to global banana production. Developing TR4-resistant banana cultivars has been challenging due to triploidy and sterility. Nevertheless, several Cavendish somaclonal variants with stable TR4 resistance have been developed and widely cultivated in Taiwan. Despite this success, the underlying genetic and molecular bases remain largely unknown, limiting the broader application of this resistance to other varieties. Here, we apply genomic and functional analyses to uncover somatic mutations and key genes associated with TR4 resistance. We observe recurrent selection for large deletions on chromosome 5 and a tendency for elevated expression of salicylic acid-responsive genes in resistant variants. Within deletion regions, we pinpoint two members of the autoinhibited Ca 2+ -ATPase ( ACA ) gene family, known negative regulators of plant immunity, as candidate susceptibility genes. Both ACA genes are downregulated in resistant variants. Silencing the ACAs in susceptible bananas enhances salicylic acid response and attenuates TR4 disease symptoms. Our study highlights the role of structural variation and copy number change of susceptibility genes like ACAs in shaping disease resistance in clonally propagated crops. Also, these findings provide a genomic framework for the development of TR4-resistant banana cultivars through targeted gene editing or selection of somatic variants.